PENGARUH PERCEIVED ENJOYMENT DAN SOCIAL INFLUENCE VARIABLES TERHADAP RESPONSE TO SOCIAL NETWORKS ADVERTISEMENTS PADA PENGGUNA INSTAGRAM DI SURABAYA - Willy Bagus Husada Bhakti (Perpustakaan Universitas Surabaya, 2019)
Abstrak - Tujuan penelitian ini untuk mengetahui pengaruh perceived enjoyment dan social influence variables terhadap response to social networks advertisements pengguna instagram di Surabaya. Penelitian ini menggunakan pendekatan kuantitatif. Responden dalam penelitian ini berjumlah 150 orang. Penelitian ini dianalisis menggunakan Structural Equation Modeling (SEM) dengan program LisWin32. Hasil penelitian ini menemukan bahwa perceived enjoyment berpengaruh signifikan terhadap social identity dan group norms. Social identity berpengaruh signifikan terhadap group intentions. Social identity tidak berpengaruh terhadap perceived advertisement relevance. Group norms tidak berpengaruh terhadap group intentions. Group intentions berpengaruh signifikan terhadap perceived advertisement relevance dan perceived advertisement value. Perceived advertisement relevance berpengaruh terhadap perceived advertisement value. Perceived advertisement relevance tidak berpengaruh terhadap response to social networks advertisements. Perceived advertisement value berpengaruh signifikan terhadap response to social networks advertisements. Kata kunci: Perceived Enjoyment, Social Influence, Advertising, Online Social Networks. Abstract - The purpose of the study was to find out the influence of perceived enjoyment and social influence variables on response to social networks advertisements of instagram users in Surabaya. This research uses quantitative approach. There were 150 respondents involved in this research. This research was analyzed using Structural Equation Modelinh (SEM) with the program LisWin32. This research found that perceived enjoyment had a significant influence on social identity and group norms. Social identity had a significant influence on group intentions. Social identity had no influence in perceived advertisement relevance. Group norms had no influence on group intentions. Group intentions had significant influence on perceived advertisement relevance and perceived advertisement value. Perceived advertisement relevance had an influence on perceived advertisement value. Perceived advertisement relevance had no influence on response to social networks advertisements. Perceived advertisement value had significant influence on response to social networks advertisments. Keywords: Perceived Enjoyment, Social Influence, Advertising, Online Social Networks.